(untitled) (Journal of Hama University, 2020)
The research aimed to find out the degree of inclusion of economic concepts in the book of social studies for the fourth grade of the basic education stage in the Syrian Arab Republic. The researcher designed a list of economic concepts that can be included in the book of social studies for the fourth grade and came out with a list of (23) concepts, the researcher followed the descriptive approach, using the unit of thought, image and activity in the analysis of the contents of the book, and obtained the following results: - Economic resources occupied the largest percentage among the economic concepts included, which got a percentage of 76.29% while trading transactions received 8.56% and economic structure 6.97% and financial transactions amounted to 7.17% - The imbalance in the inclusion of economic concepts in the book of social studies for the fourth grade basic, natural resources category got 33.86%, and tourism resources category got lower percentage (22.31%), while the rest of the other categories did not exceed ( 7.97%). - Neglecting a large section of economic concepts in the book of social studies for the fourth grade basic, such as: economic sectors, competition, expenses, debt, and others. and 9 subcategories out of 23 , do not show any impressions